Virtual Experimental Pharmacology an Alternative or Not? – A Global Assessment by Pharmacology Faculties and MBBS Students - K. Latha 2, J. Thirunavukkarasu3, C.B. Tharani 4, C. Sathish Babu1* (Recent Research in Science and Technology, 2011)
Aim: To assess the preference and acceptance of the virtual and real animal experiment in experimental Pharmacology in undergraduate students. Materials and Methods:Ã‚Â Study was conducted in practical hall in the department of pharmacology, Saveetha Medical College. Students who came for the practical class were exposed to both virtual and real animal experiments. 131 students were exposed to both virtual and experimental experiments. Four typesÃ‚Â of experiments has been exposed to the students. Virtual experiment exposed by Audio- visual aids. Real experiments were conducted by students themselves in groups of ten. Questionnaire was served to the students to find out their preference and acceptance. Questions were framed pertaining to 1. Knowledge 2. Recollection of subjectÃ‚Â Ã‚Â 3. Research. The last question was about their acceptance. Faculties were also assessed on their preference. Results: The results were analysed to find out the knowledge gained, recollection of subject, and research orientation in both virtual and experimental pharmacology. Conclusion: Virtual experiments can be an alternative to animal experiments in experimental Pharmacology in undergraduate teaching.